if g(x) = 2x squared - 8, find g to the -1 power(x)

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

if g(x) = 2x squared - 8, find g to the -1 power(x)

Algebra
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

sorry i couldnt figure out how to the squared and such lol :/
Assuming your question is given:\[g(x)=2x^2-8\]find \(g^{-1}(x)\). g(x) gives you a value for g for a given value of x. \(g^{-1}(x)\) gives you the inverse of this - i.e. given a value for g, what value of x produced this? so you need to get an expression for x in terms of g(x). the steps are as follows:\[g(x)=2x^2-8\]\[g(x)+8=2x^2\]therefore:\[2x^2=g(x)+8\]\[x^2=\frac{g(x)+8}{2}\]\[x=\pm\sqrt{\frac{g(x)+8}{2}}\]this is the inverse function and we usually replace g(x) on the right-hand-side with x, and replace the x on the left-hand-side with \(g^{-1}(x)\) to get:\[g^{-1}(x)=\pm\sqrt{\frac{x+8}{2}}\]you can check if this is correct or not by trying some values. so lets calculate g for x=2:\[g(x)=2x^2-8\]\[g(2)=2*(2)^2-8=2*4-8=8-8=0\]now lets use this value of g to calculate \(g^{-1}\):\[g^{-1}(x)=\pm\sqrt{\frac{x+8}{2}}\]\[g^{-1}(0)=\pm\sqrt{\frac{0+8}{2}}=\pm\sqrt{\frac{8}{2}}=\pm\sqrt{4}=\pm2\]so we can see that g has the value zero for either x=2 or x=-2.

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Not the answer you are looking for?

Search for more explanations.

Ask your own question